Pulse Oximetry: The impact of the computer engineer - James, Molly; Nafuna, Valeria (My University, 2023)
In 1935 Karl Mattes a professor in physiology introduced the pulse oximeter whichis a non invasive device that is used for measuring oxygen saturation level and pulserate. Pulse oximeter is based on the principle that oxyhemoglobin and deoxyhe-moglobin absorb light of different wavelength differently. The device has played ahuge role in vital remote monitoring during the COVID-19 pandemic as patientswere able to take readings at home which was a relieve to the pressure on the healthcentres. However the Center of Disease Control(CDC) reported in February 2021about the possibility of the pulse oximeter having inaccurate reading on patientswith dark skin.The role of this report is to understand the functionality and the principles onwhich the pulse oximeter works and why its less effective on patients with darkskin. Further more the report presents possible solution to the existing problem.The group constructed a pulse oximeter and carried out measuring on differentskin tones of the test subjects. The results from the reading didn’t provide enoughinformation for the group to conclude that indeed the pulse oximeter is ineffective onpatients with dark skin tone since they were inconsistent and fluctuating. Howeverfrom the research carried out by Takashi and Betsy, the group came to that thepulse oximeter is less effective on people with dark skin.